O pewnym sposobie kontroli rozumienia wybranych pojęć z analizy matematycznej przez studentów studiów matematycznych - Ciesielska, Danuta; Powązka, Zbigniew (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2017)
In the last years in Poland new standards for the matriculation examination have been established, especially in mathematics. Subsequently, for many years at the Pedagogical University of Krakow research has been conducted on difficulties that students experience in understanding the basic concepts of mathematical analysis. For the results of this research see: Powązka, Z. (2006, 2009); these are the reports of research conducted in the academic years: 2003/2004 and 2006/2007. Our main goal was to develop such a method of examination that wouls show the effectiveness of teaching without inappropriate rating, which is so typical in a standard test. The exam has a form of a standard test but the candidates give answers to four questions in one task, confirming or denying the presented thesis. We propose a new method of test scoring. Results of the test eventually give two numbers: the first is the number of correct answers given in one task, the second is the number of correct answers in the entire test. Both the numbers and order of their corresponding pairs are the basis of the final grade. The research was conducted at the Pedagogical University of Krakow at the end of the winter semester of the academic year 2010/2011, during the mathematical analysis examination test. The test was taken by 87 first year mathematics students.